The process of agricultural technology generation in Brazil: a social audit. - MACEDO, M. M. C. (1997)
The focus of agricultural technology studies in Brazil has been on technology diffusion or adoption. This approach stresses the neutrality of technology and its adoption depends on farmers' psychological and individual values. The agricultural technology generation process and the organisations in which technology is generated have not been considered as active factors. This thesis regards both as highly significant in farmers' adoption or rejection of technology. Approaches to development, modernisation and underdevelopment, along with agricultural globalisation, are the applied theoretical perspectives used to understand what happens in the underdeveloped countries in an integrated world system. This is an ex-post facto and cross-sectional study. The empirical data, based on a case study, was collected in Brazil, in and around the Brazilian Agricultural Research Organisation (EMBRAPA), a topdown state-owned organisation. Agricultural technology generation, its adoption, as well as the attitudes of users, clients, policy-makers, politicians and unions to the agricultural technology generation process were investigated. The fieldwork was conducted with eighty-seven agricultural researchers from four national agricultural research centres, one hundred and forty-four farmers, and eighty individuals and organisations' representatives. Qualitative and quantitative analyses indicated that the agricultural technology generation process is related more to scientific issues than to farmers' demands. The technology adopted by farmers was determined primarily by developments within the process of technology generation rather than through any persuasion. The thesis concludes that as a result of the process of technology generation in EMBRAP A, organised and capitalist farmers have been targeted rather than small or subsistence farmers. Therefore, the new farm as a whole research model is recommended, which explores the whole production system rather than specific agricultural products.